Letter to Jane Tolmach from John T. Conlan - John T. Conlan:::::: (1970)
A letter to Jane Tolmach from Supervisor John T. Conlan informing her of the time and date of the next Environmental Impact Study ad hoc Citizens Advisory Committee. Includes mention of the second presentation of noise data to be made by Elizabeth Cuadra and a presentation on air pollution by Litton Environmental Systems.